KONDISI LINGKUNGAN DAN STRUKTUR KOMUNITAS MANGROVE DI TELUK TOMINI, SULAWESI, INDONESIA - Rignolda Djamaluddin; Muhamad A. Kaumbo; Brama Djabar (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
The mangroves in Tomini Gulf have been exploited for chiefly conversion of mangrove areas into shrimp cultivation and extraction of mangrove wood for various purposes. In this study, interpretation to available map and satellite images and ground check were conducted to describe intertidal environment conditions and general processes of coastal dynamic. At local scale, physiographic factors were used to classify mangrove sub-habitats. A total of 159 sample points were selected to observe structure of vegetation, and the revised two ways classification of Specht was applied to classify structural classification of vegetation. The criterion of mangrove disturbance was developed to classify disturbance level. Interview and field check were conducted to assess the successfulness of implemented rehabilitation programs. Results indicated that there were obvious changes in mangrove vegetation over much the intertidal environments, and these might influence the future development and regeneration of the mangroves. While most rehabilitation programs were unsuccessful, mangrove exploitations still continued. If a sustainable management plan is not developed, the degradation will continue and spread, and the mangrove will lose its ecological functions.